The influences of territorialization on access to health services by border populations: systematic review (Research, Society and Development, 2022)
Territorialization – integrated into the National Primary Care Policy – presents principles of universality, equity and integrality. Thus, the objective was to review the influences of territorialization, on access to health services and actions, by the population residing in the Brazilian border region. A systematic review was carried out in the BVS database, between the years 2016 and 2021. 18 articles were retrieved, of which 5 were selected to compose the sample. It was found that territorialization, when not only perceived from the landscape aspect, but as a management tool for health planning, facilitates universal and equitable access to the Unified Health System, establishing a community health diagnosis, a task for which community health agents play a prominent role, favoring the community's bond with the Family Health Strategy. However, if the territory is understood as a static map, it works as an excluding factor from the right to guarantee health actions to people, as, for example, is the situation of residents in areas located on both sides of the border. From the dynamic analysis and continuing education in health, management plans can be developed that favor access to health actions by the registered and floating clientele in border regions.